(untitled) (Ágora Journal, 2025)
This article discusses the emergence of a "vivente" or "escrevivente" approach to Legal History, driven by young researchers seeking historiographical methodologies that allow them to start from their own experiences, ancestralities, affections, and political positions. The research engages with two central references: História Vivente, developed by historians from the Comunidad de Historia Vivente (Italy), and Escrevivência, a concept formulated by Conceição Evaristo based on the writings of Black Brazilian women. Both propose alternative ways of narrating and producing knowledge through experience, challenging dominant epistemologies and opening space for new ways of telling the Legal History. In opposition to the traditional paradigm of legal historiography—marked by objectivity and the distancing between subject and object—this approach incorporates an epistemological shift that acknowledges the presence of Law and History in bodies and lived experiences in the present.